A new fluorescent rhodamine B derivative as an "off–on" chemosensor for Cu2+ with high selectivity and sensitivity. Issue 5 (12th January 2016) - Meng, Xianfu; Xu, Yanxia; Liu, Jinliang; Sun, Lining; Shi, Liyi
Abstract : A novel fluorescent chemosensor containing two rhodamine B moieties per molecule was synthesized and characterized as an "off–on" fluorescent probe for copper ions. Live cell imaging experiments demonstrate its nontoxic nature in bioimaging intracellular Cu 2+ . Abstract : A novel fluorescent chemosensor containing two rhodamine B moieties per molecule was synthesized and characterized as an "off–on" fluorescent probe for the detection of copper ions (Cu 2+ ). The crystal structure of the chemosensor was confirmed by X-ray analysis and the recognition mechanism of detecting Cu 2+ was proposed with absorption and fluorescence characterization. The chemosensor showed high selectivity and sensitivity and good repetition in sensing Cu 2+, and the detection limit is as low as 38.00 nM. In addition, the chemosensor displayed low cytotoxicity as revealed by methyl thiazolyl tetrazolium (MTT) assays and was successfully applied to fluorescence test paper and living cell imaging for detecting Cu 2+ . Therefore, based on its environmental friendliness and good biocompatibility, the results offered the advantages including the detection of Cu 2+ in the environment and bioimaging of intracellular Cu 2+ .